(untitled) (Journal of EAHIL, 2025)
The paper explores the impact of artificial intelligence (AI) on Finnish health librarians and information professionals (HLIP), focusing on their attitudes and the evolving role of library services. A survey conducted in 2024 and repeated in 2025 revealed that most HLIP view AI positively, though concerns about job replacement exist. AI is used for various tasks, including translations, planning searches, and creating teaching materials. The study highlights the need for continuous skill development and adaptation to technological advancements. Despite rapid technological changes, Finnish HLIP remain confident in the relevance of their profession.